Investigation of Neem Fatty Acid Ethyl Ester for Electric Power Generation - G. Vijaya Gowri; N. Kanagaraj; C. Muniraj (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This paper presents biodiesel as an emerging renewable energy source which could meet substantially the very large growing electric energy demand maintaining the ecological balance. Biodiesel is a sustainable energy source which makes the environment out of pollution. The simplest process for biodiesel production called transesterification was carried out to produce biodiesel from neem oil. The output parameters such as speed, voltage, current and power are of the alternator are analysed for different loads using pure diesel, different biodiesel-diesel blends (80% biodiesel & 20% diesel, 60% biodiesel  & 40% diesel, 40% biodiesel & 60% diesel, 20% biodiesel  & 80% diesel) to an I.C engine. Results show that 20% biodiesel & 80% diesel blend (B20) produces the output with better efficiency. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.6978